The (Draft) European Charter of the Commons – Between Opportunities and Challenges - Anna Simonati (Central European Public Administration Review)
The concept of ownership, which (in Italy and similarly in other European systems) is still essentially based on private law rules, is currently not sufficient to ensure the satisfaction of the general interest in an increasingly wide access to scarce resources, in the perspective of equality and fairness on the field. At the same time, strong criticism has been expressed about the frequent phenomenon of privatisation of originally public assets and resources. The threats to the pursuit of the public benefit posed by privatisation may be tackled by constructing a new legal framework, aimed to protect the right of the populations to be involved not only in the use, but also in the management of the commons. An expression of this idea is the draft European Charter of the Commons, which is the result of a collective brain-storming by a group of scholars rather than a source of law. Its non-normative nature has allowed its authors to express particularly ‘brave’ positions. This article takes the Charter as a starting point to focus on some open issues. The main proposal concerns the possible exploitation of new participatory models for the involvement of communities of users in the strategic decisions on the management of the commons. In such perspective, a brief reference to the Italian legal system is made. In Italy, there are no systemic rules about the commons, but some procedures to involve the interested local communities in the strategic choices have been experimented, which can serve as an illustration also for other EU countries.